Polysiloxane surface modifier, composite current collector and preparation method of composite current collector
The polysiloxane surface modifier is prepared by co-hydrolyzing and polycondensation of activated silicone small molecules and T-series silicone. Combined with magnetron sputtering technology, the problem of insufficient binding force between the polymer base film and the metal layer in the composite fluid is solved, and the industrial production of high-performance composite fluid is achieved.
Patent Information
- Application Number
- CN202510644955.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2025-07-22
AI Technical Summary
The lack of bonding force of the existing composite fluids between the polymer base film and the metal layer leads to shedding and quality problems, and the common plating processes have problems such as environmental pollution and difficulty in controlling.
The polysiloxane surface modifier is prepared by co-hydrolyzed and polycondensed by active silicone small molecules and T-series silicone, and combined with magnetron sputtering technology to prepare high-performance composite fluid collections.
It improves the interface bonding performance, thermal stability and electrical conductivity of the composite fluid collector, and is suitable for large-scale industrial production.
Smart Images

Figure CN120349513A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metal composite current collectors used for lithium-ion battery electrodes, and particularly relates to a polysiloxane surface modifier formed by the controlled co-hydrolysis and polycondensation of a silane coupling agent, and a composite current collector prepared by modifying a polymer-based film with the polysiloxane surface modifier and a preparation method thereof. Background Art
[0002] A composite current collector (CEC) is a metal-polymer-metal "sandwich" structure functional film with a polymer film (such as polyethylene terephthalate (PET), polypropylene (PP), polyetherimide (PI), etc.) as the substrate and a metal layer (aluminum, copper) adhered to the surface. Compared with traditional single aluminum or copper metal current collectors, the polymer substrate of the composite current collector not only further reduces the overall mass of the current collector and improves the mass energy density of the current collector, but also effectively fuses and blocks when lithium branched crystals puncture or the battery is deformed and damaged, thereby cutting off the circuit to prevent the battery from experiencing thermal runaway or combustion, and ensuring the use safety of lithium-ion batteries to a certain extent. Therefore, it has a relatively wide application in current mainstream lithium-ion batteries. Currently, the commonly used composite current collectors mainly include an aluminum composite current collector with PET as the substrate and Al as the metal layer for the positive electrode of the battery, and a copper composite current collector with PP as the substrate and Cu as the metal layer for the negative electrode of the battery.
[0003] Currently, the academic and industrial circles mainly prepare composite current collectors by directly plating a metal layer on the surface of a polymer-based film. However, since the polymer and the metal form a thermodynamically incompatible system, the bonding force of the metal layer on the surface of the polymer-based film is often poor, resulting in the shedding of the composite current collector during later use. Generally speaking, the method of vacuum evaporation will cause metal atoms to splash, and the generated high temperature will cause ablation and holes on the polymer surface, or the evaporation temperature field will cause shrinkage and warping of the base film and other quality problems, seriously affecting the surface flatness of the base film, and further affecting the later metal film-forming performance and conductivity. Some scholars have proposed to prepare metal composite current collectors by wet processes such as electroless plating and electroplating, but these methods usually require the use of toxic solvents and need to carry out waste liquid post-treatment. At the same time, the flatness and density of the metal coatings obtained by wet methods are generally difficult to accurately control. Although magnetron sputtering coatings can obtain metal films with higher density, there are still challenges in aspects such as the formation mechanism of defects such as cavities and holes, preventing oxidation pollution and stress cracking.
[0004] To address the problems existing in the above-mentioned common plating processes, scholars and the industrial community have proposed introducing interfacial solubilization modifiers between the polymer-based film and the metal layer to further improve the interfacial adhesion of the composite current collector. Such as polyethylene glycol, phthalate, phosphate, acrylate, silane coupling agent, etc. Combining plasma surface treatment can enhance the bonding force between the interfacial modifier and the polymer-based film, effectively improving the adhesion between the base film and the metal layer. For example, 3-aminopropyltrimethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), (3-mercaptopropyl)trimethoxysilane (KH-590), which are commonly used in industry, hydrolyze to form linear siloxane prepolymers, forming a crosslinked network on the PET surface, providing reactive functional groups (such as -NH2, -EP, -SH) to form metal coordination bonds with the Al layer to improve the binding property. However, these silane coupling agents are often used alone in the actual production process. They are sensitive to the environment (temperature, pH value, etc.) during the hydrolysis and polycondensation process. The obtained modified layer has a low molecular weight and an uneven crosslinked network, often resulting in incomplete modification and insufficient adhesion. Although the film obtained after hydrolysis of the phthalate / acrylate coupling agent has good flexibility, and carboxyl groups can be introduced through copolymerization to further enhance the interfacial binding, the phthalate / acrylate has poor hydrolysis stability, and the structure of the formed prepolymer coating is complex and difficult to precisely control, thus easily leading to uneven coating. In addition, considering the method mentioned in some studies of using plasma treatment to pre-treat the surface of the polymer-based film first, and then using a modifier to further treat the surface of the modified polymer-based film, the plasma has high requirements for the vacuum degree of the cavity, which is difficult to achieve in the continuous large-scale production process. Therefore, this method is also difficult to popularize in industry.
[0005] Based on the above problems, there is an urgent need to explore a more effective, inexpensive, and general surface modification method. On the one hand, improve the formation of a uniform and firmly bonded modified layer with the metal layer on the surface of the polymer-based film using inexpensive and easily available modified coatings represented by polysiloxane. On the other hand, to overcome the influence of high temperature on the surface quality of the base film, a metal film is prepared by vacuum magnetron sputtering process under suitable temperature and atmosphere conditions to ensure that the metal film is flat and dense, and to improve the overall mechanical properties, corrosion resistance, and electrical conductivity of the composite current collector. Summary of the Invention
[0006] Aiming at the problems in the preparation method, the interfacial bonding performance of the finished product, and the film surface quality of the conventional composite current collector prepared from a silane-modified polymer-based film, and in order to explore a cheap and effective method for preparing a high-performance composite current collector suitable for industrial production, the present invention provides a method for improving the surface / interfacial performance of a composite current collector through siloxane co-hydrolysis surface modification and magnetron sputtering, aiming to prepare a composite current collector with strong interfacial bonding performance and surface conductivity. On the premise of maintaining the advantages of the existing process (low price, large-scale production), by performing siloxane active small molecule / silane co-hydrolysis and polycondensation modification on the surface of the polymer-based film and combining it with the magnetron sputtering aluminum film process, a high-performance composite current collector with excellent interfacial bonding performance and surface density is prepared.
[0007] The technical solution of the present invention:
[0008] The first technical problem solved by the present invention is to provide a preparation method of a polysiloxane surface modifier. The preparation method includes the following steps: (1) Mix active siloxane small molecules or linear siloxane prepolymers, T-series siloxanes, proton solutions, water, and organic acids to obtain a siloxane hydrolysis system; (2) Hydrolyze the siloxane hydrolysis system at 0-5°C, and control the pH of the system to be 3-4 during the hydrolysis process; then age at 25±2°C, 40±2°C, 50±2°C, and 60±2°C; (3) Remove the solvent to obtain the polysiloxane surface modifier.
[0009] Preferably, in step (1) of the preparation method of the above polysiloxane surface modifier, mix active siloxane small molecules or linear siloxane prepolymers, T-series siloxanes, and proton solutions to obtain solution A, mix water and organic acids to obtain solution B, and add solution B to solution A to obtain a siloxane hydrolysis system. The rate of adding solution B to solution A is 0.005-0.01 mL / s. Control the dropping rate to prevent agglomeration due to excessive partial hydrolysis.
[0010] Furthermore, in step (1) of the preparation method of the above polysiloxane surface modifier, first mix T-series siloxanes and proton solutions evenly, and then add active siloxane small molecules or linear siloxane prepolymers and mix evenly to obtain solution A. The rate of adding active siloxane small molecules or linear siloxane prepolymers is 0.01-0.1 mL / s.
[0011] Furthermore, in step (1) of the preparation method of the above polysiloxane surface modifier, solution A is prepared by mixing at 0-5°C.
[0012] Furthermore, in step (1) of the preparation method of the above polysiloxane surface modifier, the organic acid and water are mixed in a volume ratio of 0.03-0.05:100 to obtain solution B.
[0013] Further, in step (1) of the preparation method of the above polysiloxane surface modifier, the volume ratio of solution B to solution A is 20 - 50:100.
[0014] Specifically, in step (1) of the preparation method of the above polysiloxane surface modifier, the molar ratio of the active siloxane small molecule or linear siloxane prepolymer to the T-series siloxane is 2 - 5:1.
[0015] Specifically, in step (1) of the preparation method of the above polysiloxane surface modifier, the molar concentration c of silicon atoms Si = n(silane reagent) / V(proton solution) is 0.001 - 0.003 mol / mL. The ratio of the silane reagent (including the active siloxane small molecule, linear siloxane prepolymer and T-series siloxane) to the proton reagent (the molar concentration c of silicon atoms Si = n(silane reagent) / V(proton reagent)) is 0.001 - 0.003 mol / mL.
[0016] Specifically, in step (1) of the preparation method of the above polysiloxane surface modifier, the active siloxane small molecule is selected from one or more of dimethyldimethoxysilane, diethyldimethoxysilane, diphenyldimethoxysilane, perfluoropropyl dimethoxysilane.
[0017] Specifically, in step (1) of the preparation method of the above polysiloxane surface modifier, the linear siloxane prepolymer is selected from one or more of linear polydimethylsiloxane capped with silanol (HO–PDMS–OH), linear polydimethylsiloxane capped with alkoxy (RO–PDMS–OR), and poly(dimethylsiloxane) dihydroxyalkyl terminated.
[0018] Specifically, in step (1) of the preparation method of the above polysiloxane surface modifier, the T-series siloxane is selected from one or more of 3-aminopropyltrimethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), (3-mercaptopropyl)trimethoxysilane (KH-590).
[0019] Specifically, in step (1) of the preparation method of the above polysiloxane surface modifier, the proton solution is selected from one or more of anhydrous methanol, anhydrous ethanol, isopropanol, and n-butanol.
[0020] Specifically, in step (1) of the preparation method of the above polysiloxane surface modifier, the organic acid is at least one of formic acid, acetic acid, or trifluoroacetic acid.
[0021] Specifically, in step (2) of the preparation method of the above polysiloxane surface modifier, hydrolysis is carried out continuously at 0 - 5 °C for 24 - 48 h.
[0022] Specifically, in step (2) of the preparation method of the above polysiloxane surface modifier, aging is continuously carried out for 20 to 24 hours at each temperature stage of 25±2°C, 40±2°C, 50±2°C, and 60±2°C.
[0023] The second technical problem to be solved by the present invention is to provide a polysiloxane surface modifier prepared by the preparation method of the above polysiloxane surface modifier.
[0024] Furthermore, for the above polysiloxane surface modifier, the number average molecular weight (M n ) is 400 to 10,000 g / mol, and the polydispersity index DPI ≤ 1.7.
[0025] The third technical problem to be solved by the present invention is to provide a preparation method of a composite current collector. The preparation method includes the following steps: coating the obtained polysiloxane surface modifier on the surface of a polymer substrate (PS), curing to obtain a polymer substrate with a surface siloxane modification (silane modified polymersubstrate, S-m-PS); performing magnetron sputtering of a metal target on the S-m-PS to obtain a composite current collector (CEC).
[0026] Specifically, in the preparation method of the above composite current collector, the material of the polymer substrate is any one of polypropylene (PP), polyethylene terephthalate (PET), and polyetherimide (PI).
[0027] Specifically, in the preparation method of the above composite current collector, the coating method is dip coating, knife coating, or spin coating.
[0028] Specifically, in the preparation method of the above composite current collector, the curing temperature is 80 to 130°C.
[0029] Specifically, in the preparation method of the above composite current collector, the conditions for magnetron sputtering are: working vacuum pressure 10 -3 ~10 -5 Pa, sputtering pressure 0.5 to 2.5 Pa, power 70 to 150 W, and sputtering time 5 to 90 minutes.
[0030] The fourth technical problem to be solved by the present invention is to provide a composite current collector prepared by the preparation method of the above composite current collector.
[0031] Specifically, for the above composite current collector, the obtained CEC thickness ≤ 30 μm, the adhesion of the metal-polymer film interface is better than that of a conventional vapor deposition and unmodified CEC, and the surface roughness R q ≤ 30 nm.
[0032] Specifically, for the above composite current collector, the conductivity of the obtained CEC film is ≥2.07×10 6 S / m, the modulus is ≥2946.5 MPa, it has good thermal stability, and the peel resistance is improved.
[0033] Advantages of the present invention:
[0034] The present invention obtains a polysiloxane surface modifier by co-hydrolysis. Its main component is a linear polysiloxane with functional active side groups, which has an overall linear molecular structure. The number average molecular weight (M n ) is 400 - 10000 g / mol, and the polydispersity index DPI ≤ 1.7. This polysiloxane surface modifier can be used to improve the adhesion performance between the polymer-based film (PP, PET, PI, etc.) of the composite current collector and the metal layer, and can also be used to improve the barrier, heat resistance, corrosion resistance and other properties of the composite current collector.
[0035] By coating the polysiloxane surface modifier provided in the present invention on the polymer-based film, a composite current collector film with excellent interfacial adhesion, good thermal stability, high conductivity, good gas barrier property and corrosion resistance can be obtained. The preparation technology and process of this composite current collector can provide a main feasible basis for obtaining the aforementioned high-performance composite current collector. The present invention uses cheap and easily available raw materials and general methods, and is suitable for industrial-scale production of composite current collectors. The main technical parameter indicators of the obtained composite current collector are superior to those of the commercial composite current collectors of the same specifications on the current market. Description of the Drawings
[0036] Figure 1 Nuclear magnetic resonance silicon spectrum test results of the polysiloxane surface modifier in Example 1 and Comparative Example 2;
[0037] Figure 2 X-ray diffraction patterns of the composite current collector films prepared in Example 1 and Comparative Examples 1 and 2. a is the X-ray diffraction pattern of the diffraction peak from 10° to 80°, and b is the X-ray diffraction pattern of the diffraction peak from 30° to 60° after magnification of a;
[0038] Figure 3 Thermogravimetric test results of the composite current collector films prepared in Example 1 and Comparative Examples 1 and 2. a is the thermogravimetric curve, and b is the thermogravimetric derivative curve;
[0039] Figure 4 Scanning electron microscope images of the composite current collector films prepared in Example 1 and Comparative Examples 1 and 2;
[0040] Figure 5 Peel test result diagrams of the composite current collector films prepared in Example 1 and Comparative Examples 1 and 2. Detailed Embodiments
[0041] The present invention provides a method for preparing a polysiloxane surface modifier by co-hydrolysis of active siloxane small molecules / siloxanes, comprising the following steps: mixing an active siloxane small molecule or a linear siloxane prepolymer, a T-series siloxane, a proton solution, an organic acid, and deionized water to obtain an active siloxane hydrolysis system; hydrolyzing the siloxane hydrolysis system at a low temperature (0-5 °C) to carry out co-hydrolysis of the T-series siloxane with the siloxane active small molecule or the linear siloxane prepolymer, and then continuously raising the temperature (25±2 °C, 40±2 °C, 50±2 °C, 60±2 °C) for aging. During the hydrolysis process, the pH of the system is maintained at 3-4. The complete conversion of Si-O-C to Si-O-Si can be observed by infrared spectroscopy. After removing the solution by rotary evaporation, a viscous polysiloxane surface modifier can be obtained.
[0042] In the present invention, by carrying out co-hydrolysis of an active silane small molecule or a linear siloxane prepolymer with a T-series siloxane, the inhibition effect of the steric hindrance of the functional groups of the T-series siloxane and premature gelation during hydrolysis can be reduced on the premise that the raw material cost remains almost unchanged, enabling the T-series siloxane to preferentially undergo polycondensation in a linear manner, greatly improving the structural regularity of the obtained product. The addition of the active siloxane small molecule or the linear siloxane prepolymer can reduce the local concentration of the T-series silane coupling agent in the system and reduce the collision probability between silanol groups (Si-OH), thereby inhibiting the occurrence of self-condensation reactions and reducing the formation of dimers, trimers, and polymers.
[0043] In the present invention, low-temperature hydrolysis can also effectively reduce the polymerization of the silane coupling agent. In addition to using low temperature, making the pH value of the system lower can also effectively inhibit the crosslinking phenomenon during hydrolysis.
[0044] In the present invention, after gradient temperature-raising aging, Fourier transform infrared spectroscopy (FTIR) can be used to detect whether a Si–O–Si peak appears at around 1000 cm -1 and observe the intensity of the peak to judge the degree of hydrolysis and polycondensation, ensuring the full formation of the main chain of the siloxane modifier while maintaining the active functional groups on the T-series siloxane for subsequent binding to the surface of the polymer-based film.
[0045] The present invention also provides a polysiloxane surface modifier prepared by the above method, which can be used for preparing a high-performance composite current collector (CEC).
[0046] Furthermore, the obtained polysiloxane surface modifier has an overall linear molecular structure, and the number-average molecular weight (M n ) is 400-10000 g / mol, and the polydispersity index DPI ≤ 1.7.
[0047] Furthermore, the obtained polysiloxane surface modifier has active groups such as amino (-NH2), epoxy group (-EP), mercapto group (-SH), etc., which can increase the bonding strength between the polymer-based film and the metal layer.
[0048] The present invention also provides a high-performance composite current collector (CEC) material. The polysiloxane surface modifier is coated on the surface of a polymer substrate (PS), and the coating is cured under high-temperature conditions to obtain a silane-modified polymer substrate (S-m-PS); the S-m-PS is subjected to magnetron sputtering with different metal targets, and the magnetron sputtering parameters are adjusted to obtain a composite current collector (CEC) with a corresponding metal layer.
[0049] Furthermore, the obtained CEC has a thickness ≤ 30 μm, the adhesion of the metal-polymer film interface is better than that of a conventional evaporated and unmodified CEC, and the surface roughness R q ≤ 30 nm.
[0050] Furthermore, the obtained CEC film has a conductivity ≥ 2.07×10 6 S / m, a modulus ≥ 2946.5 MPa, good thermal stability, and improved peel resistance.
[0051] The following further illustrates the technical solutions of the present invention through specific examples, which do not limit the present invention. Those skilled in the art can reasonably design the technical solutions with reference to the examples and can also obtain the results of the present invention.
[0052] Example 1
[0053] 1. Preparation of co-hydrolyzed polysiloxane surface modifier
[0054] Weigh 6.37 g of γ-glycidoxypropyltrimethoxysilane (KH-560) and add it to a three-necked flask containing 48 mL of absolute ethanol. Mechanically stir at 0 °C until the silane is uniformly dispersed in the solvent; weigh 4.8 g of dimethoxydimethylsilane (DMDS) and slowly add it to the three-necked flask at a rate of 0.1 mL / s. Mechanically stir at 0 °C until the silane small molecules are uniformly dispersed in the solvent;
[0055] Take a small amount of acetic acid to adjust the pH of 12 mL of deionized water to about 3, and load the stabilized acidic solution into a constant-pressure funnel. Slowly drip it into the three-necked flask at a rate of 0.01 mL / s; the system is mechanically stirred at 0 °C for 24 h, heated to 25 °C and mechanically stirred for 24 h, and continuously stirred and aged for 24 h at 40 °C, 50 °C, and 60 °C respectively;
[0056] Take out the aged solution and rotary evaporate it at 70 °C until 80% of the solvent is removed. Put the modifier solution obtained by rotary evaporation into a refrigerator at 5 °C for storage.
[0057] 2. Surface modification of PET
[0058] Mix the above modifier with an appropriate amount of absolute ethanol in a volume ratio of 3:1 and ultrasonically disperse for 10 min;
[0059] Put a PET film with a thickness of 10 μm into a solution of deionized water and absolute ethanol mixed in a volume ratio of 1:1, ultrasonically clean for 5 min, take it out and rinse with absolute ethanol until no impurities adhere to the surface. Put the cleaned PET into a petri dish for standby;
[0060] Adopt the dip coating method, immerse the PET film in the modifier solution for 1 min, take it out and scrape off the excess solvent on the surface with a scraper, and then put it into a vacuum oven;
[0061] Dry at 60 °C for 2 h to make the modifier adhere evenly; cure at 90 °C for 6 h to obtain a surface-modified PET film.
[0062] 3. Magnetron sputtering aluminum film
[0063] Fix the modified PET film on the magnetron sputtering sample stage;
[0064] Under the condition of a vacuum degree of 3.5×10 -4 Pa, introduce argon at 40 sccm and control the sputtering pressure to be 1.0 Pa;
[0065] Adjust the radio frequency power to 100 W and the sputtering time to 10 min to obtain a composite current collector with an aluminum film thickness of about 100 nm.
[0066] The properties of the polysiloxane surface modifier obtained in this example and the finally prepared composite current collector are shown in Table 1 below.
[0067] Table 1
[0068]
[0069] The test results show that the aluminum film of the prepared composite current collector has high adhesion on the PET base film, the metal film is uniform and dense, and has excellent mechanical properties and corrosion resistance; the saturated peel strength is increased by 11.4% and 7.4% respectively compared with Comparative Example 1 without using a silane coupling agent modification and Comparative Example 2 using only KH560 single coupling agent modification samples.
[0070] Example 2
[0071] 1. Preparation of co-hydrolyzed polysiloxane surface modifier
[0072] Weigh 5.30 g of (3-mercaptopropyl)trimethoxysilane (KH-590) and add it to a three-necked flask containing 24 mL of absolute ethanol. Mechanically stir at 0 °C until the silane is uniformly dispersed in the solvent; weigh 4.8 g of dimethoxydimethylsilane (DMDS) and slowly add it to the three-necked flask at a rate of 0.1 mL / s. Mechanically stir at 0 °C until the silane small molecules are uniformly dispersed in the solvent;
[0073] Take a small amount of acetic acid to adjust the pH of 12 mL of deionized water to about 3, and load the stabilized acidic solution into a constant pressure funnel. Slowly add it dropwise to the three-necked flask at a rate of 0.01 mL / s; stir the system mechanically at 0 °C for 24 h, heat up to 25 °C and mechanically stir for 24 h, continue stirring and age for 24 h at 40 °C, 50 °C, and 60 °C respectively;
[0074] Take out the aged solution and rotary evaporate it at 70 °C to remove 80% of the solvent. Put the modified agent solution obtained by rotary evaporation into a refrigerator at 5 °C for storage.
[0075] 2. Surface modification of PET
[0076] Same as Example 1
[0077] 3. Magnetron sputtering aluminum film
[0078] Same as Example 1
[0079] The performance of the obtained polysiloxane surface modifier and the finally prepared composite current collector is shown in Table 2 below.
[0080] Table 2
[0081]
[0082] The test results show that the aluminum film of the prepared composite current collector has high adhesion on the PET base film, the metal film is uniform and dense, and has excellent mechanical properties and corrosion resistance; the saturated peel strength is increased by 8.6% and 2.1% compared with Comparative Example 1 without using silane coupling agent modification and Comparative Example 3 using only KH590 single coupling agent modification and non-low temperature reaction.
[0083] Comparative Example 1
[0084] Put a PET film with a thickness of 10 μm into a solution of deionized water and absolute ethanol mixed by volume ratio of 1:1, ultrasonically clean for 5 min, take it out and rinse with absolute ethanol until there is no impurity attachment on the surface. Put the cleaned PET into a petri dish for standby;
[0085] Fix the PET film on the magnetron sputtering sample stage;
[0086] At a vacuum degree of 3.5×10 -4Argon was introduced at 40 sccm under Pa conditions, and the sputtering pressure was controlled at 1.0 Pa;
[0087] The radio frequency power was adjusted to 100 W, and the sputtering time was 10 min to obtain a composite current collector with an aluminum film thickness of about 100 nm.
[0088] The properties of the obtained composite current collector are shown in Table 3 below.
[0089] Table 3
[0090]
[0091] Comparative Example 2
[0092] 1. Preparation of a single polysiloxane surface modifier
[0093] Weigh 15.81 g of γ-glycidoxypropyltrimethoxysilane (KH-560) and add it to a three-necked flask containing 48 mL of absolute ethanol. Stir mechanically at 0 °C until the silane is uniformly dispersed in the solvent;
[0094] Take a small amount of acetic acid to adjust the pH of 12 mL of deionized water to about 3, and put the stabilized acidic solution into a constant pressure funnel. Slowly drip it into the three-necked flask at a rate of 0.01 mL / s; The system was mechanically stirred at 0 °C for 24 h, heated to 25 °C and mechanically stirred for 24 h, and continuously stirred and aged at 40 °C, 50 °C, and 60 °C for 24 h each;
[0095] Take out the aged solution and rotary evaporate it at 70 °C to remove 80% of the solvent. Put the modified agent solution obtained by rotary evaporation into a refrigerator at 5 °C for storage.
[0096] 2. PET surface modification
[0097] Same as Example 1;
[0098] 3. Magnetron sputtering of aluminum film
[0099] Same as Example 1;
[0100] The properties of the obtained polysiloxane surface modifier and the finally prepared composite current collector are shown in Table 4 below.
[0101] Table 4
[0102]
[0103] Comparative Example 3
[0104] 1. Preparation of a single polysiloxane surface modifier under non-low temperature conditions
[0105] Weigh 15.52 g of (3-mercaptopropyl)trimethoxysilane (KH-590) and add it to a three-necked flask containing 24 mL of absolute ethanol. Take a small amount of acetic acid to adjust the pH of 12 mL of deionized water to about 3, and put the stabilized acidic solution into a constant pressure funnel, and slowly drip it into the three-necked flask at a rate of 0.01 mL / s; the system is mechanically stirred at 40 °C for 24 h, continuously stirred and aged at 50 °C and 60 °C for 24 h each;
[0106] Take out the aged solution and rotary evaporate it at 70 °C until 80% of the solvent is removed, and put the modifier solution obtained by rotary evaporation into a refrigerator at 5 °C for storage.
[0107] 2. PET surface modification
[0108] Same as Example 1;
[0109] 3. Magnetron sputtering aluminum film
[0110] Same as Example 1;
[0111] The properties of the obtained polysiloxane surface modifier and the finally prepared composite current collector are shown in Table 5 below.
[0112] Table 5
[0113]
[0114] Performance test:
[0115] The obtained polysiloxane surface modifier and the finally prepared composite current collector are tested as follows:
[0116] The prepared polysiloxane surface modifier was measured for its molecular weight and molecular weight distribution using a gel permeation chromatograph (GPC, Agilent 1260). The mobile phase was tetrahydrofuran, the flow rate was 1 mL / min, and the polydispersity index of the polysiloxane surface modifier was measured at 35 °C. The final test results are shown in the attached tables of each example and comparative example. The results show that the polydispersity index of Example 1 in the co-hydrolysis system is 1.23, which is 0.22 lower than that of Comparative Example 2 without the co-hydrolysis system. The polydispersity index of Example 2 is 0.16 lower than that of Comparative Example 3 without temperature control and single hydrolysis system. It shows that the present invention regulates the polymerization reaction rate through co-hydrolysis, thereby controlling the molecular chain dispersion uniformity of the silane modifier, and further regulating the uniform attachment of the modifier on the surface of the polymer matrix.
[0117] The prepared polysiloxane surface modifier was used 29 Si nuclear magnetic resonance spectroscopy (NMR, Bruker BioSpin GmbH) was used to observe the hydrolysis state of the silane coupling agent. The final test results are as Figure 1 shown. Among them, the spectrum of Comparative Example 2 mainly shows T2 (δ = -58.62 ppm), T 3 (δ = -67.69 ppm) peak, indicating that a crosslinked silicon-oxygen network was formed during the condensation of KH-560, while the addition of D in the spectrum of Example 1 2 (δ = -20.9 ppm) peak, indicating that the degree of crosslinking in Example 1 was lower than that in Comparative Example 2, improving the toughness of the modifier and forming an interface layer with both organic and inorganic characteristics, which helped to improve the polymer-metal interface performance of the composite current collector.
[0118] The final composite current collector film was observed for the aluminum film formation using X-ray diffraction (XRD, TD-3500). The final test results are as follows Figure 2 shown. Diffraction signals of the aluminum crystal (111) and (200) crystal planes appeared at 38.6° and 45.0° respectively. Among them, the peak intensity of Example 1 was significantly higher than that of Comparative Example 1 and Comparative Example 2, indicating that the co-hydrolyzed polysiloxane modifier in Example 1 optimized the orientation arrangement of aluminum grains, thereby improving the local crystallization order. The Scherrer formula was used to calculate the grain size on the surface of the composite current collector. The calculation results are shown in the attached tables of each example and comparative example. The grain sizes of Example 1 and Example 2 were 9.68 nm and 8.90 nm respectively, which were improved compared with the comparative examples. Among them, in Comparative Example 1, due to the weak binding at the PET-Al interface, the growth of aluminum grains during nucleation was inhibited by the interface stress and defects, forming fine and disordered grains; while in Example 1, the organic-inorganic interface layer formed by the co-hydrolyzed modifier not only provided a more uniform nucleation substrate for aluminum grains, but also released the interface stress through chemical bonding, promoting the preferential growth of grains along specific crystal planes, and finally obtaining a more uniform and stable aluminum layer.
[0119] The final composite current collector film was observed for the surface morphology and roughness using atomic force microscopy (AFM). The final test results are shown in the attached tables of each example and comparative example. The roughness of Example 1 and Example 2 was improved compared with that of Comparative Example 1. Appropriate surface roughness can improve the binding force of electrode active materials. If the surface roughness is too low, the active layer is likely to peel off due to volume expansion or mechanical stress during charge and discharge, resulting in capacity attenuation and shortened cycle life; the roughness of Example 1 and Example 2 was significantly reduced compared with that of Comparative Example 2 and Comparative Example 3, indicating that the co-hydrolyzed polysiloxane and precise control of the hydrolysis process improved the uniformity of the modifier.
[0120] The final composite current collector film was subjected to thermogravimetric analysis (TG-DTG, METTLER 1100LF), and the thermal performance was tested at a heating rate of 20 °C / min in the range from room temperature to 800 °C. The final test results are as follows Figure 3 (a)(b) shown. From Figure 3(a) Judging from the thermogravimetric curve, the structures of Example 1 and Comparative Examples 1 and 2 were relatively stable below 400 °C, and no obvious volatilization or decomposition occurred; they decomposed rapidly at 400 - 500 °C, and the residual weight of Example 1 increased compared with that of Comparative Examples 1 and 2; after carbonization at 800 °C, the carbon residue of Example 1 was 33.3%, which was increased by 8.3% and 4.6% respectively compared with those of Comparative Examples 1 and 2. It is proved that the polysiloxane surface modifier obtained by the co-hydrolysis enhances the high-temperature stability of the composite current collector. This effect is shown in Figure 3 (b) This was further verified in the thermogravimetric differential curve. Sharp weight loss rate peaks appeared between 450 - 550 °C for all three, and the peak intensity of Example 1 was significantly lower than that of the comparative examples, indicating that the co-hydrolysis siloxane modification effectively delayed the kinetic process of the decomposition reaction.
[0121] The mechanical properties of the finally prepared composite current collector film were tested. The film was cut into rectangular specimens with dimensions of 5×0.5 mm, and tensile tests were carried out on an electronic universal testing machine (MTS, E42.503) with a gauge length of 10 mm and a tensile rate of 5 mm / min. The elongation at break and modulus of the specimens were calculated, and the final test results are shown in the attached tables of each example and comparative example. The elongation at break of Example 1 was 33.68%, which was increased by 27.92% and 22.01% respectively compared with those of Comparative Example 1 and Comparative Example 2; the modulus of Example 1 was 2946.5 MPa, which was increased by 700.7 MPa and 684.8 MPa respectively compared with those of Comparative Example 1 and Comparative Example 2.
[0122] The resistance of the finally prepared composite current collector film was measured using a multi-channel digital recorder (Keithlely Instruments, Series 2400), and the conductivity of the composite current collector was calculated. The final test results are shown in the attached tables of each example and comparative example. The conductivities of Example 1 and Example 2 were 2.07×10 6 S / m and 2.16×10 6 S / m respectively, which were relatively flat compared with Comparative Example 1, indicating that the modifier had little effect on the conductivity of the composite current collector; and compared with Comparative Example 2 without co-hydrolysis and without regulating the hydrolysis process, the conductivity increased.
[0123] The micro-morphology of the finally prepared composite current collector film was analyzed using a scanning electron microscope (SEM, Thermo scientific Apreo 2C). The final test results are shown in Figure 4As shown in the figure. Under a 5-μm field of view, the aluminum particles on the surface of Example 1 were evenly distributed, with relatively uniform particle spacing and no obvious defects; while in Comparative Example 1, the distribution density was uneven, and there were phenomena of sparse or enriched particles in local areas. In Comparative Example 2, there were holes and a small amount of massive protrusions, proving that single silane modification may lead to uneven structure due to local over-crosslinking of siloxane chains. Further magnified observation showed that the particle size of Example 1 was smaller and arranged tightly and orderly, indicating that co-hydrolysis modification could better control the process of uniform nucleation and film formation of aluminum on its surface; in contrast, the particle sizes in Comparative Example 1 were significantly different, and Comparative Example 2 showed the coexistence of particle agglomeration and irregular morphology.
[0124] The peeling experiment test of the finally prepared composite current collector film was carried out by the tape peeling method. The tape used was 3M 2144 crepe paper of 3M China Limited. The tape was cut into a size of 20×10 mm and adhered to the surface of the composite current collector for peeling. The final test results are as Figure 5 shown. Compared with the comparative examples, the aluminum layer peeled off on the crepe paper of Example 1 was significantly reduced, indicating that the co-hydrolyzed polysilane surface modifier of the present invention significantly improved the interfacial properties between PET and aluminum. The present invention aims at the problems of insufficient modification efficiency and uniformity of traditional silane-modified composite current collectors and poor quality of metal coatings, and provides a polysiloxane surface modifier obtained by controlling the co-hydrolysis process at low temperature and a method for preparing a composite current collector. The main component of the polysiloxane surface modifier is a linear polysiloxane with functional active side groups. The polysiloxane surface modifier can be used to improve the adhesion performance between the polymer matrix film and the metal layer of the composite current collector, and can also be used to improve the barrier, heat resistance, corrosion resistance and other properties of the composite current collector. Compared with traditional composite current collectors and composite current collectors modified with single silane coupling agents, the method of the present invention regulates the hydrolysis state of siloxane, and introduces active siloxane small molecules to carry out co-hydrolysis and polycondensation with T-series trifunctional siloxanes to prepare a polysiloxane surface modifier, so as to better balance the controllability and applicability of modification. The composite current collector prepared with the polysiloxane surface modifier of the present invention has the advantages of strong bonding force, good thermal stability and excellent mechanical properties, and has the excellent characteristics of competitive growth of polymorphic nuclei on the surface of the modified polymer matrix and forming a high-density film layer.
Claims
1. A preparation method of a polysiloxane surface modifier, characterized in that: It includes the following steps: (1) Mix active siloxane small molecules or linear siloxane prepolymers, T-series siloxanes, a proton solution, water, and organic acids to obtain a siloxane hydrolysis system; (2) Hydrolyze the siloxane hydrolysis system at 0 - 5 °C, controlling the pH of the system to be 3 - 4 during the hydrolysis process; then age at 25 ± 2 °C, 40 ± 2 °C, 50 ± 2 °C, and 60 ± 2 °C; (3) Remove the solvent to obtain the polysiloxane surface modifier.
2. The preparation method of the polysiloxane surface modifier according to claim 1, characterized in that: In step (1), mix active siloxane small molecules or linear siloxane prepolymers, T-series siloxanes, and a proton solution to obtain solution A, mix water and organic acids to obtain solution B, and add solution B to solution A to obtain a siloxane hydrolysis system; Further, first mix the T-series siloxanes and the proton solution evenly, and then add active siloxane small molecules or linear siloxane prepolymers and mix evenly to obtain solution A; Furthermore, solution A is prepared by mixing at 0 - 5 °C.
3. The preparation method of the polysiloxane surface modifier according to claim 1 or 2, characterized in that: In step (1), the active siloxane small molecules are selected from one or more of dimethyldimethoxysilane, diethyldimethoxysilane, diphenyldimethoxysilane, perfluoropropyl dimethoxysilane; the linear siloxane prepolymers are selected from one or more of linear polydimethylsiloxane capped with silanol, linear polydimethylsiloxane capped with alkoxy, and linear polydimethylsiloxane capped with hydroxyhydrocarbon; the T-series siloxanes are selected from one or more of 3-aminopropyltrimethoxysilane, γ-glycidyletheroxypropyltrimethoxysilane, (3-mercaptopropyl)trimethoxysilane; Further, the molar ratio of the active siloxane small molecules or linear siloxane prepolymers to the T-series siloxanes is 2 - 5:
1.
4. The preparation method of the polysiloxane surface modifier according to any one of claims 1-3, characterized in that: In step (1), the proton solution is selected from one or more of anhydrous methanol, anhydrous ethanol, isopropanol, and n-butanol; Further, the molar concentration c of silicon atoms Si = n(silane reagent) / V(proton solution) is 0.001 - 0.003 mol / mL.
5. The preparation method of the polysiloxane surface modifier according to any one of claims 1-4, characterized in that: In step (1), the organic acid is at least one of formic acid, acetic acid, or trifluoroacetic acid; Further, the organic acid and water are mixed in a volume ratio of 0.03 - 0.05:100 to obtain solution B.
6. The preparation method of the polysiloxane surface modifier according to any one of claims 1-5, characterized in that: In step (2), continue hydrolysis at 0 - 5 °C for 24 - 48 hours.
7. The preparation method of the polysiloxane surface modifier according to any one of claims 1-6, characterized in that: In step (2), continue aging at each temperature stage of 25 ± 2 °C, 40 ± 2 °C, 50 ± 2 °C, and 60 ± 2 °C for 20 - 24 h.
8. A polysiloxane surface modifier prepared by the preparation method of the polysiloxane surface modifier according to any one of claims 1 - 7.
9. A composite current collector, characterized in that: Coat the polysiloxane surface modifier according to claim 8 on the surface of a polymer-based membrane, and cure it to obtain a polymer-based membrane with surface siloxane modification; the polymer-based membrane with surface siloxane modification is prepared by magnetron sputtering of a metal target.
10. The composite current collector according to claim 9, wherein: The conditions for magnetron sputtering are as follows: the working vacuum pressure is 10 -3 to 10 -5 Pa, the sputtering pressure is 0.5 to 2.5 Pa, the power is 70 to 150 W, and the sputtering time is 5 to 90 min.